Planning Flow Shop Scheduling - Kavaliauskas, Donatas; Sakalauskas, Leonidas (Jaunųjų mokslininkų darbai, 2020)
Various planning problems often arise in production design and management: planning of resources, raw materials, personnel. These problems fall into the complexity class of NP fullness. It is not enough to use greedy algorithms to get the optimal solution, heuristic algorithms must be used. One of heuristic algorithms is the branch and bound algorithm. This algorithm is a computer-simulated solution to the problem of flow shop. The paper presents several variants of the flow shop planning problem, for which the branch and bound algorithm has been adapted.
Keywords: optimization; branch and bound algorithm; flow shop